Perceptions Of The Surau Gadang Community, Nanggalo District, Padang City Towards Forensic Autopsies In Terms Of Knowledge, Religion And Culture - Fitratul Annisa; Rika Susanti; Roni Eka Sahputra (International Journal of Medicine and Health, 2024)
Forensic autopsy is an examination of a corpse including external and internal examinations aimed at determining the cause of death. The number cases of rejection forensic autopsies in the community is caused by knowledge, religion, and culture. This study aims to view the perception of the people of Surau Gadang Village towards forensic autopsies in terms of knowledge, religion, and culture. This study was a descriptive study by using cross-sectional design. Sampling collection with simple random sampling technique. The primary data was taken by questionnaire with 99 respondents is the people of Surau Gadang Village who had met the inclusion criteria. Results: The results showed that from 99 people there were 84 female respondents (84,8%) with the most age range 19-39 years (57,6%) and most of the respondents have high school education or equal (59,6%). The results of the questionnaire data showed that most respondents had a low level of knowledge (41.4%), religious perception was good (80.8%) and cultural perception was good (77.8%). The perception of the people of Surau Gadang Village towards forensic autopsies in terms of knowledge is low, but in terms of religion and culture the perceptions are good.